Comparison of Capillary and Venous Plasma Drug Concentrations After Repeated Administration of Risperidone, Paliperidone, Quetiapine, Olanzapine, or Aripiprazole. Issue 6 (17th August 2016) - Remmerie, Bart; De Meulder, Marc; Ariyawansa, Jay; Savitz, Adam
Abstract: Quantification of blood levels of antipsychotic drugs may be useful for managing medication therapy. This open‐label, parallel‐group study was performed to compare finger‐stick‐based capillary with corresponding venous plasma concentrations for risperidone, paliperidone, quetiapine, olanzapine, and aripiprazole and their major metabolites after repeated dosing in patients with schizophrenia or related illnesses. Finger‐stick‐based capillary and venous blood samples were collected at various times within a dosing interval. All drug concentration measurements in the derived plasma samples were performed with validated liquid chromatography–tandem mass spectrometry methods. Finger‐stick‐based capillary and venous plasma drug concentrations after repeated dosing were generally similar. Olanzapine capillary plasma concentrations, however, were on average approximately 20% higher than venous concentrations, with a trend for a relatively greater difference occurring shortly after dosing. In addition, smaller capillary–venous differences were observed for extended‐release and long‐acting intramuscular formulations and for aripiprazole, a drug with a long half‐life, compared with drugs administered as an immediate‐release formulation (risperidone, olanzapine). After repeated dosing, plasma derived from finger‐stick‐based blood was observed to be predictive of the venous concentrations. Capillary sampling may be an appropriate alternative to venous sampling to readily evaluate systemic drug concentrations.